Developing Qualitative Research Methodology: Using Focus Groups as a Single Research Method in a Student Motivation Study - Al Kaabi, Sultan Ali (Advances in Social Sciences Research Journal, 2017)
This paper presents the process that was used to design a research method for a study using focus groups as the main data collection method to investigate male students’ experience of higher education in the United Arab Emirates (UAE). The methodology design process covered research paradigm, ontology, epistemology, and research characteristics and considerations. The alignment between research question and research method was then explored followed by the justification for using focus groups as the only method to conduct the study.